2016
DOI: 10.4028/www.scientific.net/amm.855.75
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Determination of Maturity of the Monthong Durian by Mel-Frequency Cepstral Coefficients (MFCCs) and Neural Network

Abstract: The challenging for buyers around the globe to identify good quality of Durian. For several kinds of Durian, it may be difficult for buyers to determine the Durian quality by appearance. The ability to select only good quality Durian without cutting or cleaving is useful because buyers will not waste money ordering undesirable Durian.This paper proposes a nondestructive technique to determine the stages of maturity of durian fruits. The presented methodology utilizes the concept of pattern matching. We used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The Convolutional layer is denominated from the important linear mathematical operation in the layer, so-called convolution, or filtering. The convolution function is described in (9). ( , )…”
Section: Convolutional Neural Network For Voice Imagementioning
confidence: 99%
“…The Convolutional layer is denominated from the important linear mathematical operation in the layer, so-called convolution, or filtering. The convolution function is described in (9). ( , )…”
Section: Convolutional Neural Network For Voice Imagementioning
confidence: 99%
“…It has been reported that audio data converted to MFCC can be effectively classified for sound classification [ 16 ], because the potentially available phonetic information is included to facilitate feature classification. Therefore, MFCCs have acoustic features that have been widely used in various applications [ 10 , 17 , 18 , 19 ]. As deep learning-based classification models have shown capabilities of high accuracy and reliability in various fields [ 20 , 21 ], the models have a high potential for effectively classifying animal vocals that contain behavioral meanings.…”
Section: Introductionmentioning
confidence: 99%